2018
DOI: 10.1590/s1678-9946201860008
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological characteristics of cutaneous lesions caused by Leishmania Viannia panamensis in Panama

Abstract: Cutaneous leishmaniasis (CL) is an endemic disease in the Republic of Panama, caused by Leishmania (Viannia) parasites, whose most common clinical manifestation is the presence of ulcerated lesions on the skin. These lesions usually present a chronic inflammatory reaction, sometimes granulomatous, with the presence of lymphocytes, plasma cells and macrophages. This study describes the histopathological characteristics found in the skin lesions of patients with CL caused by Leishmania (V.) panamensis in Panama.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 44 publications
1
27
0
1
Order By: Relevance
“…The variable “keratynocites in epidermis” (Figure 8b) can follow the same analysis; lower values can be related with the presence of a more necrotic scab and so that to death cells. This behavior agrees with the transition from active phase to ulcerative one during the formation of a cutaneous ulcer caused by CL: the dermis passes from a proliferation of keratinocyte to keratinocyte cell death [29,51]. In respect to p -values, the results obtained for the variables “epidermis thickness” and “keratynocites in epidermis” in correlation groups 1 to 4 are statistically significantly different from those obtained in correlation groups 6 to 9.…”
Section: Resultssupporting
confidence: 75%
“…The variable “keratynocites in epidermis” (Figure 8b) can follow the same analysis; lower values can be related with the presence of a more necrotic scab and so that to death cells. This behavior agrees with the transition from active phase to ulcerative one during the formation of a cutaneous ulcer caused by CL: the dermis passes from a proliferation of keratinocyte to keratinocyte cell death [29,51]. In respect to p -values, the results obtained for the variables “epidermis thickness” and “keratynocites in epidermis” in correlation groups 1 to 4 are statistically significantly different from those obtained in correlation groups 6 to 9.…”
Section: Resultssupporting
confidence: 75%
“…These histopathological aspects also differ from cutaneous lesions caused by dermotropic species of the parasite in the New World, such as Leishmania (L.) amazonensis , Leishmania (V.) braziliensis, Leishmania (V.) guyanensis and Leishmania (V.) panamensis . These findings reinforce the role of the parasite in determining the clinical and immunohistopathological features of the infection .…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, Couppié et al observed that cutaneous lesions caused by Leishmania (V.) guyanensis are characterized by a non‐granulomatous diffuse inflammatory infiltrate mainly composed of lymphocytes, histiocytes and plasma cells as well as numerous intrahistiocytic forms of Leishmania . Finally, lesions caused by Leishmania (V.) panamensis are characterized by an intense inflammatory infiltrate in the dermis with diffuse and lymphohistiocytic predominance, a lymphoplasmacytic and granulomatous presentation pattern with the presence of ulcers, acanthosis, exocytosis and spongiosis in the epidermis …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have evaluated the potential of PNPs as therapeutic tool against E. coli urinary tract infections. Related to this, Ashmore and colleges compared the antibacterial efficacy of polymer-coated silver NPs with the non-coated ones [ 104 ]. The coating of silver NPs with polymer significantly improves the antibacterial efficacy of the particles.…”
Section: Recent Polymeric Nanoparticles Against Most Common Human Bacmentioning
confidence: 99%